2015
DOI: 10.1002/polb.23923
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3‐hexylthiophene) films prepared using binary solvent mixtures

Abstract: Binary solvent mixtures were routinely used to induce the hierarchical assembly of poly(3-hexylthiophene) (P3HT) in the liquid phase. This technique has garnered a lot of interest as a route to well-organized films and composites, but, to date, the impact that the attributes of the liquid-phase aggregates and solvent mixtures have on the organization of the films have only been partially scrutinized. The molecular weight and concentration dependence of P3HT assembly in three binary solvent mixtures containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…We observed similar ellipsoidal and fibrous film morphologies in a previous investigation of P3HT films, and it is well‐known that these markedly different structures are attributable to variations in the crystallinity of P3HT . P3HT fibers are representative of highly crystalline packing modes from extensive, well‐ordered π–π stacking of P3HT along the a ‐axis in Figure (b).…”
Section: Resultssupporting
confidence: 78%
“…We observed similar ellipsoidal and fibrous film morphologies in a previous investigation of P3HT films, and it is well‐known that these markedly different structures are attributable to variations in the crystallinity of P3HT . P3HT fibers are representative of highly crystalline packing modes from extensive, well‐ordered π–π stacking of P3HT along the a ‐axis in Figure (b).…”
Section: Resultssupporting
confidence: 78%
“…Our work focuses on the use of solvent mixtures to (1) direct the assembly of P3HT into aggregate nanostructures prior to film processing and (2) manipulate the organization of P3HT during film processing . The use of binary solvent mixtures to induce aggregation of P3HT is particularly promising because the physical and chemical characteristics of the mixtures can be systematically adjusted by varying the composition of the good and poor solvents, thereby providing access to solvent characteristics that may not be available with pure solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in our lab showed that evaporation rates and evaporation rate differences alone cannot rationalize the variations of the structural motifs and morphologies of films processed from the solvent mixtures . Polymer solubility and solubility differences are particularly relevant to films cast from solvent mixtures and must be carefully and methodically scrutinized.…”
Section: Resultsmentioning
confidence: 98%